PENGARUH KOMPENSASI FINANSIAL DAN STRES KERJA TERHADAP KINERJA MITRA DRIVER OJEK ONLINE DI BALI - Ni Ketut Dian Pratiwi; Made Yudi Darmita (Universitas Triatma Mulya, 2020)
The rapid development of the world of information technology has brought tremendous benefits for the progress of human civilization. Even humans are now able to adapt and participate in developing and utilizing these technologies. Starting from the communication system, electronic system, banking system, even things that were not thought of before, which is used as a motorcycle taxi support. This was then developed further so that online motorcycle taxis were created. This study aims to analyze and prove the effect of financial compensation and work stress on the performance of online motorcycle taxi driver partners. This study took a sample in Bali. The sample technique used is incidental sampling technique. The number of respondents used 100 online motorcycle taxi driver partners. Multiple linear regression analysis using SPSS software version 23. The regression equation obtained: Y = 31.250 + 0.529X1 - 0.316X2. The results of this study indicate that; First, financial compensation has a positive effect on the performance of online motorcycle taxi driver partners in Bali. Second, work stress has a negative effect on the performance of online motorcycle taxi driver partners in Bali. Fourth, the amount of influence contributed by financial compensation and work stress on the performance of online motorcycle taxi driver partners in Bali was 54.4%.